Adverse effect signature extraction and prediction for drugs treating COVID-19 - Wang, Han; Wang, Xin; Li, Teng; Lai, Daoyuan; Zhang, Yan Dora (Frontiers in Genetics, 2022)
Given the considerable cost of drug discovery, drug-repurposing is becoming attractive as it can effectively shorten the development timeline and reduce the development cost. However, most existing drug-repurposing method omitted the heterogeneous health conditions of different COVID-19 patients. In this study, we evaluated the adverse effect (AE) profiles of 106 COVID-19 drugs. We extracted four AE-signatures to characterize the AE distribution of 106 COVID-19 drugs by non-negative matrix factorization (NMF). By integrating the information from four distinct databases (AE, bioassay, chemical structure, and gene expression information), we predicted AE profiles of 91 drugs with inadequate AE feedback. For each pair of drug clusters, discriminant genes accounting for mechanisms of different AE signatures were identified by Sparse linear discriminant analysis. Our findings can be divided into three parts. First, drugs abundant with AE-signature 1 (for example, Remdesivir) should be taken with caution for patients with poor liver, renal or cardiac functions, where the functional genes accumulate in RHO GTPases Activate NADPH Oxidases pathway. Second, drugs featuring AE-signature 2 (for example, Hydroxychloroquine) are unsuitable for patients with vascular disorders, with relevant genes enriched in signal transduction pathways. Third, drugs characterized by AE-signature 3 and 4 have relatively mild AEs. Our study showed that NMF and network-based framework contribute to more precise drug recommendations.